A Conceptual Restructuring of Spatial Motion Expressions in Chinese L2 - Sparvoli, Carlotta (Frontiers in Psychology, 2018)
This paper focuses on the patterns in the encoding of spatial motion events that play a major role in the acquisition of these type of expressions. The goal is to single out the semantic contribution of the linguistic items which surface in Chinese locative constructions. In this way, we intend to provide learners with an account of the spatial representation encoded in the Chinese language. In fact, Chinese grammar is often perceived as idiosyncratic, thus generating a frustration that turns into learned helplessness (Maier and Seligman 1976). We will analyse Talmy’s (2000) framework under the light of investigations such as Landau and Jackendoff (1993), Svenonius (2004, 2006, 2007), Terzi (2010). It will be shown that in Chinese locative structures, the Axial Part information is signalled by localizers and can be specified only when the Ground is considered as an object with “axially determined parts” (Landau and Jackendoff 1993). Thus, we will elaborate on present account on the localizer’s function (Peyraube 2003, Lamarre 2007, Lin 2013) by showing that the localizer highlights an axially determined part within a reference object, consistently with Terzi (2010) definition of Place, and with Wu (2015) decomposition of Place into Ground and Axial Part. Moreover, it will be shown that the preposition zài ‘at’ encodes a Locative type of Motion event (Talmy 2000), thus, it is not semantically vacuous. Other categories will be presented, such as the semantic class of positional verbs (Huang 1987). We will indicate the contexts wherein such notions can trigger the conceptual restructuring which enables adult learners to switch from L1 “thinking for speaking” to L2 “thinking for speaking” (Slobin 1987).